Penggunaan Media Bahan Alam Untuk Meningkatkan Kreativitas Anak - Meta Octa Riany; Retno Wulandari; Fahmi (CV. ITTC INDONESIA, 2023)
This action research aims to increase the creativity of children aged 5-6 years with the help of natural media. This research was conducted at Kindergarten Kemala, Palembang. The action research method was carried out in two cycles consisting of planning, action, observation and reflection. The subject is PAUD children who have problems with creativity. Based on the results of this study, it can be concluded that the hypothesis is accepted. From this it is concluded that the use of natural materials can increase the creativity of children aged 5-6 years.